Fermentation conditions increasing protease production by Serratia marcescens in fresh whey - UstárizFrancisco|; Laca, Adriana; García, Luis; Díaz, Mario (Rev. Téc. Fac. Ing. Univ. Zulia)
Extracellular protease production in fresh whey fermented by Serratia marcescens was increased by studying the influence of the most important physico-chemical operating variables. Fermentations were carried out in Erlenmeyer flask and in an automatic controlled bioreactor (Bioflo III), obtaining in the latter case the highest protease levels (8,800 EU/mL Ó 484 DS) when working under optimized conditions. Two kinds of proteases were determined in the supernatant, a major metalloprotease (84%Ó 2 DS) and a minor serine protease (13%+/-2 DS). In all cases cell growth and protein degradation were modelled, and the effect of oxygen concentration on cell growth was determinate by Bioflo III and was also modelled.